Agricultural management intensity drives niche partitioning of ammonia oxidizers at three contrasting soil sites - Yu Zeng; Che Tan; Chang Yin; Xiaozhong Wang; Hongsheng Gao; Hua Peng; Yongchao Liang (Applied Soil Ecology, 2026)

Grassland management pattern affects soil organic carbon content but not its mineralization on the Qinghai-Tibetan Plateau - Yizhe Peng; Jianjun Cao; Jan F. Adamowski; Asim Biswas; Hong Wang; Yiyang Peng; Xiaoqing Yang; Xinhao Deng; Xiongwei Zeng (Applied Soil Ecology, 2026)

From genomic functional potential to rhizosphere ecological networks: Bacillus velezensis BER1–mediated regulatory mechanisms underlying rice growth promotion - Zitong Kang; Ziwei Jiao; Sasa Zhang; Xiaoxing Wang; Yuquan Wei; Ruihong Wang; Yuan Chang; Xiaoyan Ding; Ning Wang (Applied Soil Ecology, 2026)

Study on the infiltration mechanism of extreme rainfall under typical vegetation coverage in the three gorges reservoir area - Can Wei; Ruihong Wang; Dongbin Cui; Kaiqiang Zhao; Ruhao Li; Xianda Yi (Bulletin of Engineering Geology and the Environment, 2026)

Chiglitazar alleviates cognitive dysfunction in diabetic mice by restoring mitochondrial function via the PPARs/Nrf2 signaling pathway - Junfang Yuan; Yuzhong Wang; Defeng Wang; Yanfeng Zhen; Yanan Sun; Li Wang; Hui Fang (Metabolic Brain Disease, 2026)

Cooperation between cellulose-degrading complex microflora and enzymes on improving soil organic carbon turnover and stabilization in the saline-alkali soils - Sainan Gao; Xuelian Liu; Chong Wang; Haoyue Qin; Honghao Cheng; Xueya Liu; Mengli Liu (Applied Soil Ecology, 2026)

Biochar-mediated microbial community and functional shifts regulate soil organic carbon fractions, enhancing carbon accumulation and stabilization in a subtropical plantation soil - Ting Li; Hongzhi Yang; Yuxin Tan; Mengzhu Jiang; Dechao Wu; Xiaoyong Chen; Wensheng Liu; Yelin Zeng; Kuan Peng; Yonghong Wang; Chan Chen; Guangjun Wang; et al. (Applied Soil Ecology, 2026)

Moisture-driven restructuring of nematode energy channels orchestrates soil multifunctionality during treeline migration - Shuwang Song; Yan Tao; Xindong Feng; Jingdi Xu; Xinchang Kou; Shengzhong Wang (Applied Soil Ecology, 2026)

Carbon availability and redox potential regulate carbon mineralization in peat soils under contrasting moisture regimes - Guangyuan Xu; Jiye Cai; Yuting Wang; Yang Wang; Junxiao Pan; Zucheng Wang; Hongkai Li; Yanmin Dong; Shasha Liu; Ziping Liu; Zhiwei Xu; Shengzhong Wang (Applied Soil Ecology, 2026)

Sulfur-cycle microorganisms regulate soil aggregate dynamics in saline-alkali soils - He Hu; Jia Cao; Mengli Liu; WenLiang Wu; Chong Wang (Applied Soil Ecology, 2026)

Interfacial microbial communities drive litter decomposition along elevation gradients in Segrila Mountain - Mengyao Dong; Wenzu Liu; Hongfang Ma; Ruihong Wang; Xinjun Zhang; Zhuonan Hou; Daqing Luo; Heping Ma; Bin Zhao; Yuquan Wei (Applied Soil Ecology, 2026)

Climate and soil nutrients jointly affect the variations in microbial nutrient limitation with elevation in sedge peatlands - Tao Zhang; Yimeng Wang; Ming Wang; Shengzhong Wang; Guodong Wang; Meiling Zhao; Jingci Meng; Yusong Yuan; Nanlin Hu (Applied Soil Ecology, 2025)

Terrain-driven heterogeneity of soil microbial ecosystems in western pastoral areas - Wenlong Zhang; Zhicong Ma; Tianxiang Chen; Jiakun Wang; Jianou Hua; Yipeng Wu; Zhixiang Zhu; Zi Yin; Chong Wang; Xiaoshi Wei (Applied Soil Ecology, 2025)

Enhanced microbial network stability and biogeochemical cycles in saline-alkali soil through simplified prokaryotes and complex fungal networks - Ruihong Wang; Hao Qin; Zhijian Shi; Mengben Wang; Junjian Li (Applied Soil Ecology, 2025)

Organic carbon mineralization and its temperature response of soil organic matter fractions in the Yellow River estuary wetland - Guowei Lu; Jisong Yang; Qixuan Wang; Wei Zhao; Zhikang Wang; Xuehong Wang; Bo Guan; Di Zhou; Kai Ning (Applied Soil Ecology, 2025)

Vermicompost and Azotobacter chroococcum amendment of saline-alkali soil decreases nitrogen loss and increases nitrogen uptake confirmed by ZmNRT1.1B of maize - Siping Li; Chong Wang; Huiying Huang; Lei Zhao; Jia Cao; Mengli Liu (Applied Soil Ecology, 2025)

Microbial inoculants drive disease suppression and rhizosphere modulation for effective management of pepper phytophthora blight - Muye Xiao; Xuchen Liu; Xiaozhong Wang; Wencai Lu; Tong Zhang; Yuheng Yang (Applied Soil Ecology, 2025)

Ammonia-oxidizing microorganisms overwhelm denitrifiers in determining the efficacy of DMPP in upland soils - Jilin Lei; Donghan Yang; Yingying Sun; Saihong Wang; Qianyi Fan; Junhui Yin; Rui Liu; Qing Chen (Applied Soil Ecology, 2025)

Chronosequence changes in soil microbes under Populus simonii × P. nigra stands: Implications for soil health restoration in Mollisols - Jia Yang; Qinghua Liu; Keyi Liu; Shunzhong Wang; Huiyan Gu (Applied Soil Ecology, 2025)

Identifying bacterial fixation pathway of mediating soil carbon stock changes along tropical forest restoration - Mingliu Wang; Shaojun Wang; Mei Lu; Minkun Chen; Zhe Zhang; Hong Wang (Applied Soil Ecology, 2025)

Warming-induced response of microbial diversity and functions regulated microbial necromass and soil multifunctionality - Zhuonan Hou; Wenzu Liu; Shaoqi Xu; Su Chang; Xinjun Zhang; Ruihong Wang; Daqing Luo; Baorong Wang; Shaoshan An; Yuhui Qiao; Zhangliu Du; Yuquan Wei (Applied Soil Ecology, 2025)

Vermicompost enhances the salt tolerance of maize by reshaping the rhizosphere microenvironment - Mengli Liu; Jia Cao; Chong Wang; Binglei Wang; Rui Xue (Applied Soil Ecology, 2024)

A review on sox genes in fish - Yacheng Hu; Binzhong Wang; Hejun Du (Reviews in Aquaculture, 2021)
The Sry‐related high mobility group box ( Sox ) genes family is a group of transcription factors playing crucial roles during reproduction and development. At least 50% amino acid sequences of Sox protein family are similarity to the sex‐determining region on the Y chromosome (Sry). The sox family exists throughout the invertebrates and vertebrates and plays an important role in sex determination and differentiation, gonadal development, neurogenesis, formation of multiple tissues and organs, early embryonic development, chondrocyte differentiation, cardio‐vascular system, and other features in fish. The full characters of sox genes at the genome‐wide level have been reported in many fish species, due to the rapid development of high‐throughput DNA sequencing technique and massive accumulation of genomic data. Here, the research progress of fish sox gene family is reviewed to provide the latest information for the research in this field.

Pelagic microalgae as suitable diets for the benthic harpacticoid copepod Tigriopus japonicus - Guizhong Wang; Jie Xu; Chaoshu Zeng; Qilong Jia; Lisheng Wu; Shaojing Li (Hydrobiologia, 2015)